2016
DOI: 10.1111/andr.12196
|View full text |Cite
|
Sign up to set email alerts
|

Is phytoestrogen intake associated with decreased risk of prostate cancer? A systematic review of epidemiological studies based on 17,546 cases

Abstract: SUMMARYThis study uses current epidemiological data to evaluate whether phytoestrogen intake is associated with a reduced risk of prostate cancer. We performed a random-effect meta-analysis of published data retrieved from PubMed, Web of Science, ProQuest, and CNKI, which was supplemented by a manual search of relevant references. Study quality was assessed using the Newcastle-Ottawa Scale (NOS). Subgroup analysis and meta-regression were performed to explore the source of heterogeneity. Sensitivity analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
(57 reference statements)
1
18
0
2
Order By: Relevance
“…This hypothesis has further been supported by four previous meta-analyses of epidemiological studies, all of which showed a protective association between soy consumption and PCa [ 10 , 11 , 12 , 13 ]. However, these meta-analyses did not integrate and evaluate all available existing studies pertaining to both dietary soy food intake and circulating levels of isoflavones.…”
Section: Introductionsupporting
confidence: 60%
“…This hypothesis has further been supported by four previous meta-analyses of epidemiological studies, all of which showed a protective association between soy consumption and PCa [ 10 , 11 , 12 , 13 ]. However, these meta-analyses did not integrate and evaluate all available existing studies pertaining to both dietary soy food intake and circulating levels of isoflavones.…”
Section: Introductionsupporting
confidence: 60%
“…Similar patterns have been observed in our study, and they likely contributed and will continue to contribute to racial disparity in PCa survival negatively affecting AA men. The underlying cause for this race-dependent variation in PCSM benefit associated with dose-escalation is unclear, and it may be the result of a combination of socioeconomic [ 15 ], hormonal [ 16 - 17 ], dietary [ 18 - 19 ] and genetic factors [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…ENL has been shown to activate estrogen receptors α and β of the prostate in vivo [ 6 ], and may also, for example, modulate the bioavailability of steroidal hormones through competitive binding to sex hormone binding globulin (SHBG) [ 7 ]. Several studies have shown protective associations between intake of PE-rich foods, calculated intake of PE and levels of PE in blood or urine, and risk of prostate cancer [ 8 ], but most of these findings have been due to isoflavones, which are not generally consumed in large amounts in Europe and North America [ 8 , 9 ]. International prospective studies have found no association between serum ENL and prostate cancer [ 10 , 11 ], but a recent meta-analysis by He and Wang et al [ 12 ], including 2 population-based case–control and 4 nested case–control studies, did provide support for a protective association (OR for highest vs. lowest ENL category 0.76, 95% confidence interval 0.60–0.97), although the support from the population-based case–control studies was stronger than that from the nested case–control studies.…”
Section: Introductionmentioning
confidence: 99%